(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The article examines key areas of digital transformation in logistics based on McKinsey data and industry analytics. Particular attention is given to the adoption of AI, IoT, 5G, and cloud solutions that enhance the transparency and efficiency of supply chains. The findings show that automation, demand forecasting, and route optimization deliver the greatest impact. Digital ecosystems are becoming a strategic factor shaping the competitiveness of logistics companies.